3D self-supported hierarchical NiCo architectures with integrated capacitive performance and enhanced electronic conductivity for supercapacitors. (1st October 2016) - Tang, YanRu; Cheng, Baohai
Abstract: 3D self-supported hierarchical Ni and Co co-hydroxide architectures are promising electrode materials for supercapacitor application attributed to their prominent properties such as binder-free electrode fabrication process and high power density. However, the intrinsic conductivity of Ni and Co co-hydroxide is poor. How to develop a new type of supercapacitors exhibiting enhanced electronic conductivity and involving pseudocapacitive performance and electric double-layer capacitive performance is still challenging. Herein, we present a facile co-electrodeposition method to fabricate self-standing Nix Co2x (OH)y @Ni/ITO monolithic electrode by growing a layer of Nix Co2x (OH)y with layered structure on surface of conductive Ni nanotube, which increases specific surface area and prompts fast ion adsorption/de-adsotption (electrochemical double layer capacitance performance) and fast surface redox reactions (pseudo-capacitance performance). With the conductive Ni nanotube as current collector and electronic conductor, the binder-free Nix Co2x (OH)y @Ni/ITO electrode exhibits high specific capacitance (92.4 mF cm −2 at 0.1 mA cm −2, the mass of active material per cm −2 is typically in 100 s μg). Moreover, Nix Co2x (OH)y @Ni/ITO hybrids display excellent cycling stability with 93.3% capacitance retention after 5000 cycles. The results suggest Nix Co2x (OH)y @Ni/ITO nanostructure constructed based on integrated features of pseudocapacitive performance and electric double-layer capacitive performance and enhanced electronic conductivity is expected to be a type of excellent electrode material for supercapacitor. Graphical abstract: Highlights: NiCo electrode is fabricated by growing layered structure on Ni nanotube surface. The layered structure prompts fast ion adsorption/de-adsotption and redox reactions. The Ni nanotube serves as nanostructured current collector and electronic conductor. The NiCo hybrids display 93.3% capacitance retention after 5000 cycles.